EVALUATION AND INHERITANCE OF SINGLE AND MULTIPLE RESISTANCE TO VIRAL DISEASES OF COWPEA (Vigna unguiculata (L.) Walp) (2015)
Viral diseases usually occur as multiple infections and significantly reduce yield in cowpea. Planting resistant cowpea varieties is economical and effective in controlling viral diseases. However, information on mode of inheritance of virus resistance required for cowpea breeding programmes is limited. Thus, single and multiple resistance and inheritance patterns of resistance to viral diseases were investigated in some selected cowpea breeding lines. Nine cowpea genotypes comprising eight improved lines and Ife brown (susceptible check) were evaluated for resistance to Bean common mosaic virus-blackeye cowpea mosaic strain (BCMV-BlCM), Southern bean mosaic virus (SBMV) and Cucumber mosaic virus (CMV) in Screenhouse and Field Experiments (SaFE) in IITA, Ibadan. Virus identity was confirmed by RNA sequence similarity search in GenBank databases using BLASTN. Cowpea seedlings were mechanically inoculated seven days after sowing with viruses in 8 viral treatments comprising single and mixed infections. Pots were arranged in 8 by 9 factorial experiment in a completely randomised design (r=3). Disease incidence and severity data were taken at weekly intervals for eight Weeks Post-Inoculation (WPI). Cowpea leaf samples were tested for viruses at five WPI using Enzyme Linked Immunosorbent Assay with negative results confirmed by Polymerase Chain Reactions. Yield parameters were taken while seeds from infected cowpea plants were tested for seed-transmitted viruses. In field evaluations, cowpea lines were planted (r=4) using inoculated Ife brown as spreader rows. Cowpea lines were classified into resistant/susceptible plants using data from disease severity, area under disease progress curves and virus detection test. Two resistant/tolerant and two susceptible cowpea lines were selected and crossed. Parental lines, F1, F2, BC1 and BC2 were evaluated for virus resistance. Data were analysed using chi-square, ANOVA and PPMC at p=0.05. Virus identity revealed 92%, 95% and 98% homology to SBMV, BCMV-BlCM and CMV respectively. Disease severity in SaFE was negatively correlated with number of pods/plant (r= -0.9, -0.8), seeds/pod (r= -0.8,-0.6) and total seed weight (r= -0.6,-0.7). Higher seed transmission rates were observed for CMV (2-26%) and BCMV-BlCM (2- 25%) than SBMV (0-2%). Cowpea line IT98K-1092-1 had multiple-resistance to BCMVBlCM and SBMV and tolerance to CMV while IT97K-1042-3 showed multiple-resistance to BCMV-BlCM and SBMV. Lines IT97K1069-6 and IT04K-405-5 showed single UNIVERSITY OF IBADAN LIBRARY iii resistance to SBMV. However, IT99K-1060 and IT98K-503-1 were susceptible to the three viruses while other genotypes were susceptible to one or two viruses. Goodness-offit for 1 resistant to 3 susceptible segregation ratios ( 2 =1.28) indicated that inheritance of resistance to BCMV-BlCM is controlled by a single recessive gene pair in IT97K-1042-3. Segregation ratios 15 resistant to 1 susceptible plants ( 2 =0.30 and 1.39) suggested that duplicate dominant genes conditioned resistance to SBMV and tolerance to CMV in IT98K-1092-1. Reciprocal crosses supported the monogenic and digenic natures of inheritance and indicated absence of maternal or cytoplasmic effects. Some cowpea lines showed single resistance to Southern bean mosaic virus while some had multiple-resistance to the viruses. Inheritance patterns were monogenic or digenic. The most promising line can be released as a new variety after further trials or its resistance genes introgressed into a susceptible higher yielding variety. Keywords: Multiple-resistance, Bean common mosaic virus, Southern bean mosaic virus,Cucumber mosaic virus, Cytoplasmic effects. Word count: 499